Comparison of S. aureus Proteomic Profiles from Biofilm and Planktonic Growth Conditions using 2D- Gel Electrophoresis. - Assafi, Mahde S. A. (Science Journal of University of Zakho, 2016)
Bacteria growing as biofilms are distinct from the same bacteria growing as planktonic cells. Biofilms cells show increased resistance to antimicrobial, immunological, predatory, and chemical attack than planktonic cells. Most studies on bacterial diseases use planktonic bacteria. The objective of this study was to identify expressed proteins that are unique to Staphylococcus aureus biofilm mode of growth. S. aureus was grown in tryptic soy broth and Dulbecco’s modified eagle medium at biofilm and planktonic growth conditions. Protein samples were cleaned up and separated according to their electrophoretic mobility using 7 cm IPG strips (pH 3–10 and pH 4–7) on 2D gel electrophoresis. Expressed proteins of both growth conditions were compared. Data analysis revealed that the expression of S. aureus proteins from planktonic and biofilm was higher in TSB media than DMEM media. Biofilm growth condition showed higher intensity of expressed proteins and new expressed proteins were observed. One protein was found to be upregulated in planktonic growth condition. Additionally, the majority of the proteins were clustered in the area of acidic region (pH 4–7). 2D-gel electrophoresis is a powerful and widely used method for the proteomic analysis. Biofilms represent a realistic representation of bacterial behavior and organisms are capable of altering their physiology in the surrounded environments. The results could help to illustrate the differences in pathogenesis between biofilm and planktonic cells in any model of disease. This will identify biological markers to improve the diagnostics, treatment, and prevention of S. aureus biofilms.